LIN7A is a major determinant of cell-polarity defects in breast carcinomas. Issue 1 (December 2016) - Gruel, Nadège; Fuhrmann, Laetitia; Lodillinsky, Catalina; Benhamo, Vanessa; Mariani, Odette; Cédenot, Aurélie; Arnould, Laurent; Macgrogan, Gaëtan; Sastre-Garau, Xavier; Chavrier, Philippe; Delattre, Olivier; Vincent-Salomon, Anne
Abstract Background Polarity defects are a hallmark of most carcinomas. Cells from invasive micropapillary carcinomas (IMPCs) of the breast are characterized by a striking cell polarity inversion and represent an interesting model for the analysis of polarity abnormalities. Methods In-depth investigation of polarity proteins in 24 IMPCs and a gene expression profiling, comparing IMPC (n = 73) with invasive carcinomas of no special type (ICNST) (n = 51) have been performed. Results IMPCs showed a profound disorganization of the investigated polarity proteins and revealed major abnormalities in their subcellular localization. Gene expression profiling experiments highlighted a number of deregulated genes in the IMPCs that have a role in apico-basal polarity, adhesion and migration.LIN7A, a Crumbs-complex polarity gene, was one of the most differentially over-expressed genes in the IMPCs. Upon LIN7A over-expression, we observed hyperproliferation, invasion and a complete absence of lumen formation, revealing strong polarity defects. Conclusion This study therefore shows that LIN7A has a crucial role in the polarity abnormalities associated with breast carcinogenesis.